2010
DOI: 10.1364/oe.18.024516
|View full text |Cite
|
Sign up to set email alerts
|

Continuous wave Nd:YAG channel waveguide laser produced by focused proton beam writing

Abstract: We report on mirrorless continuous wave laser oscillation at 1064 nm from a 808 nm pumped Nd:YAG optical channel waveguide fabricated by 1 MeV focused proton beam writing. Pump power threshold has been found to be 94 mW with a laser slope efficiency of 40%. A maximum output power at 1064 nm for the waveguide laser is 63 mW at absorbed pump power of 247 mW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 27 publications
(39 reference statements)
1
11
0
Order By: Relevance
“…Moreover, swift-ion-irradiated Nd:YAG waveguide laser systems have similar performances (laser slope efficiencies of 16% and pump power thresholds of 38.3 mW) than the ion implanted samples (Ren et al, 2010a(Ren et al, , 2011a. (Yao et al, 2010).…”
Section: Waveguide Lasersmentioning
confidence: 98%
See 3 more Smart Citations
“…Moreover, swift-ion-irradiated Nd:YAG waveguide laser systems have similar performances (laser slope efficiencies of 16% and pump power thresholds of 38.3 mW) than the ion implanted samples (Ren et al, 2010a(Ren et al, , 2011a. (Yao et al, 2010).…”
Section: Waveguide Lasersmentioning
confidence: 98%
“…For the first system, they found that the fluorescence properties of both Ce and Nd ions (including the energy transfer between them) were not significantly affected by the waveguide formation processing. Afterwards, Tan et al (Tan et al, 2010) showed generation of continuous wave lasers at a wavelength of ~1064 nm in Nd:YAG implanted with C 3+ at room temperature. Similar results were obtained for N 3+ -implanted Nd:YAG crystals by Ren et al (Ren et al, 2011a).…”
Section: Yttrium Aluminum Garnet (Y 3 Al 5 O 12 or Yag)mentioning
confidence: 99%
See 2 more Smart Citations
“…Waveguide lasers have been realized in Nd:YAG crystals in the systems manufactured by ion beam implantation/irradiation [3][4][5][6][7][8][9] or femtosecond laser inscription [10][11][12][13]. Recently, the irradiation of swift heavy ions (i.e., with energy higher than 1 MeV/amu) has emerged to be a powerful and available technique to fabricate optical waveguide owing to the reduced irradiation fluences and larger refractive index changes for waveguide formation [4,14].…”
Section: Introductionmentioning
confidence: 99%